2017
DOI: 10.2169/internalmedicine.56.7320
|View full text |Cite
|
Sign up to set email alerts
|

A Mesenteric Desmoid Tumor with Rapid Progression

Abstract: We herein report the case of a rapidly progressive sporadic mesenteric desmoid tumor (DT). A 62-year-old woman presented with a 4-cm-diameter palpable mass in the left supraumbilical area. The mass showed an ill-defined margin with heterogeneous delayed enhancement on computed tomography and heterogeneous high intensity on T2-weighted magnetic resonance imaging. Sixteen months after the initial observation, the mass had grown in size, reaching 13 cm in diameter. The resected mass was histologically confirmed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…In our study, most desmoid tumors showed a mass forming or infiltrative shape with moderate or marked homogeneous enhancement and rarely seen calcification or necrosis in the masses. These findings were similar and consistent with previous reports (10,11,18). Recently, several MRI features of desmoid tumors have been reported and some researchers have correlated the various signal intensities of the mass on the T2-weighted images with histopathologic findings such as cellular, collagen, and myxoid components through the excellent soft tissue contrast resolution of MRI (6,14,19).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In our study, most desmoid tumors showed a mass forming or infiltrative shape with moderate or marked homogeneous enhancement and rarely seen calcification or necrosis in the masses. These findings were similar and consistent with previous reports (10,11,18). Recently, several MRI features of desmoid tumors have been reported and some researchers have correlated the various signal intensities of the mass on the T2-weighted images with histopathologic findings such as cellular, collagen, and myxoid components through the excellent soft tissue contrast resolution of MRI (6,14,19).…”
Section: Discussionsupporting
confidence: 91%
“…They can arise from any part of the body and are classified into the intraabdominal, abdominal wall, and extra-abdominal subtypes according to location (8,9). Although histologically benign, desmoid tumors are often locally invasive and associated with a high local recurrence rate after resection (3,10). They are generally asymptomatic; however, various symptoms occur as a result of the compressive or obstructive effects on other organs (2,3,11).…”
Section: Introductionmentioning
confidence: 99%
“…Intra-abdominal DTs' incidence significantly differs between sporadic and FAP-related cases: only 5% of sporadic DTs are intra-abdominal ones, whereas 80% of [36][37][38].…”
Section: Intra-abdominal Dtmentioning
confidence: 93%
“…Intra-abdominal DTs’ incidence significantly differs between sporadic and FAP-related cases: only 5% of sporadic DTs are intra-abdominal ones, whereas 80% of cases of FAP-related DTs are intra-abdominal (especially mesenteric ones) [ 36 38 ].…”
Section: Intra-abdominal Dtmentioning
confidence: 99%
“…DT may arise at various sites, including the extremities, trunk and abdomen. However, the incidence of intra‐abdominal disease differs between sporadic (5%) and FAP (80%) cases 3 . Most patients with intra‐abdominal tumours present with mild painful mass, nausea, early satiety, intestinal obstruction or functional deterioration of an ileoanal anastomosis in FAP patients who had a colectomy 4 .…”
Section: Figmentioning
confidence: 99%